Second‐order differential equations for the power converters dynamical performance analysis. (22nd February 2022) - Amoroso, Eleonora; Bonanno, Gabriele; D'Aguí, Giuseppina; De Caro, Salvatore; Foti, Salvatore; O'Regan, Donal; Testa, Antonio
Abstract : The paper is devoted to the study of a second‐order differential equation of type Sturm‐Liouville with coefficients sign changing, and the existence of one positive solution is obtained by requiring a specific growth of the nonlinearity. In particular, this study is useful in the analysis of the dynamical performance of a class of power converter.